2000
DOI: 10.1038/sj.cr.7290039
|View full text |Cite
|
Sign up to set email alerts
|

Human μ-opioid receptor overexpressed in Sf9 insect cells functionally coupled to endogenous Gi/o proteins

Abstract: Human m-opioid receptor (H OR) with a tag of six consecutive histidines at its carboxyl terminus had been expressed in recombinant baculovirus infected Sf9 insect cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Since the human A-opioid receptors expressed in Sf9 cells showed a pharmacological profile similar to those described in mammalian cells (Massotte et al, 1997(Massotte et al, , 1999, the baculovirus/insect cell system provides a viable alternative for large receptor production. We have previously expressed human A-opioid receptors in Sf9 cells and demonstrated that these recombinant A-opioid receptors were functionally coupled to the endogenous G i/o proteins (Wei et al, 1998(Wei et al, , 2000. It provides a cellular model to study the effect of opiates.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since the human A-opioid receptors expressed in Sf9 cells showed a pharmacological profile similar to those described in mammalian cells (Massotte et al, 1997(Massotte et al, , 1999, the baculovirus/insect cell system provides a viable alternative for large receptor production. We have previously expressed human A-opioid receptors in Sf9 cells and demonstrated that these recombinant A-opioid receptors were functionally coupled to the endogenous G i/o proteins (Wei et al, 1998(Wei et al, , 2000. It provides a cellular model to study the effect of opiates.…”
Section: Discussionmentioning
confidence: 96%
“…Infection was performed in monolayer at a cell density of 2 Â 10 6 by recombinant baculoviruses containing human A-opioid receptor cDNA as previously described (Wei et al, 1998(Wei et al, , 2000. Cells were harvested at the peak time of production (60-64 h after the infection).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous functional studies of a number of human GPCRs transiently expressed in both Sf9 and High Five™ cell lines showed agonist responses either leading to an elevation of intracellular Ca2+ concentrations (Kuhn et al, 1996) or a decrease in intracellular cAMP levels (Jansson et al, 1995;Obermeier et al, 1996;Wei et al, 2000), implying the presence of endogenous insect Gαq-like and Gαi-like α subunits, respectively. This is in full accord with our data.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 94%
“…The effect of F9204 was similar to morphine which effect was more potent and longer than that of F9202. Ohmefentanyl which is the most potent analgesic so far [28], has 8 isomers (F9201-F9208). F9202 and F9204 had similarly potent analgesic action, but showed a large difference in physical dependence [23].…”
Section: Discussionmentioning
confidence: 99%